A method of estimating ball drop area using AE measurement - Kamijima, K.; Itoh, K.; Ushiyama, Y.; Shioiri, A.; Gao, P. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
To develop a system that can analyze the hitting area of a table tennis player in real time, we propose a method of estimating the ball drop from the acoustic emissioniAEj generated when the ball drops on the table. In previous studies using micro AE sensors, it was established that the ball drop area can be reliably estimated if it is within a radius of 50 mm from the sensor. However, for practical applications, multiple sensors are required that makes the signal processing complicated. We have comprehensively detected the AE waves generated from a playing table using broadband AE sensors, and proposed a technique for estimating the ball drop area more efficiently. We installed AE sensors at four locations on one side of the playing table. Coordinates were created for 56 points located at intervals of 20 cm from the origin along the x and y axes. The ball was allowed to drop freely three times from a height of the 16 cm on each coordinate. The AE waves generated from the table were amplified using a preamplifier. The output signal was fed into an oscilloscope, and the peak values of the waveform were recorded. The AE waves could be detected for a wider range using our experimental setup compared to smaller sensors. Furthermore, the AE waves became larger for ball drop areas closer to the sensor, thereby indicating a possibility of estimating the ball drop area.